The Influence of Human Capital and Organizational Citizenship Behavior (OCB) on Performance with Organizational Commitment as A Mediating Variable in Paramedics at The Health Center of The South Leitimur Sub-Distric of Ambon City - Elvata Minoa Kakisina; Conchita. V. Latupapua; A. Risambessy (STKIP Yapis Dompu, 2023)
The purpose of this study was to determine the Effect of Human Capital & OCB on Performance and Organizational Commitment at the Leitimur Selatan Health Center - Ambon City with a total of 76 medical staff respondents. Judging from the results of this study it is proven that the influence of human capital has no significant effect on performance. This result can be seen from the t-statistics value on the path coefficient test where the t-count value is 1.881, which is smaller than the t-table 1.96 and the p-value is 0.061 greater than the criterion of 0.05. Human capital has no significant effect on organizational commitment These results can be seen from the t-statistics value in the path coefficient test where the t-count value is 0.816 which is smaller than the t- table of 1.96 and the p-value of 0.415 is greater than the criterion of 0.05. Organizational commitment has a positive and significant effect on the performance of medical personnel. These results can be seen from the t- statistics value in the path coefficients test where the t-value of 2.698 is greater than the t-table of 1.96 and the p-value of 0.007 is smaller than the criterion of 0.05. Organizational citizenship behavior has a positive and significant influence on the performance of medical personnel. These results can be seen from the t-statistics value in the path coefficient test where the t-count value is 2.205 which is greater than the t-table of 1.96 and the p- value is 0.028 which is smaller than the criterion of 0.05. Organizational citizenship behavior has a positive and significant influence on organizational commitment. These results can be seen from the t-statistics value in the path coefficients test where the t-count value is 3.199 which is greater than the t-table of 1.96 and the p-value of 0.001 is smaller than the criterion of 0.05.